2006
DOI: 10.2134/agronj2005.0181
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth and Yield of Cotton Planted at Various Densities and Configurations

Abstract: Cotton (Gossypium hirsutum L.) lint yield stability across a range of plant populations, coupled with expensive transgenic cotton seed, makes reduced seeding rates an attractive cost-saving option. Studies evaluated plant populations and seeding configurations in an effort to: (i) isolate a specific combination that minimizes seed use without sacrificing yield, and (ii) identify potential growth and development changes associated with cotton grown at these densities. Cotton planted in studies conducted during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
7
19
0
1
Order By: Relevance
“…Seed cotton yield in the latest planting at the highest plant density was significantly higher than the lowest plant density, as evident in Table 3. Similar results have been found by other researchers (Jones and Wells, 1998;Siebert et al, 2006;Wrather et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…Seed cotton yield in the latest planting at the highest plant density was significantly higher than the lowest plant density, as evident in Table 3. Similar results have been found by other researchers (Jones and Wells, 1998;Siebert et al, 2006;Wrather et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…It is affected by both crop and soil management factors. Corn produces taller plants at high plant population (Jonathan, et al, 2006). Soil moisture availability (Hussain et al, 1999), soil compaction, surface soil structure, and soil aggregation (Kladivko et al, 1986), fertilizer applications (Kapusta et al, 1996), and tillage system (Kladivko et al, 1986) also influence plant height of corn.…”
Section: Introductionmentioning
confidence: 99%
“…O'Berry et al [10] reported that cotton yields were highest with plant populations of 8.9 and 12. McCarty et al [11] reported that plant spacing of 8,15,23, and 30 cm resulted in similar yields in 2003, but yields were significantly affected by plant spacing in 2004. Pettigrew et al [12] in a study with obsolete and modern cotton genotypes grown at densities of five plants m −2 and 10 plants m −2 reported there was no difference in yield between the two densities.…”
mentioning
confidence: 99%